ANALYSIS OF USING CODE MIXING OF FACEBOOK POSTED BY THAI USERS - Sakilah Tohheh (E-LINK JOURNAL, 2021)
The study is mainly the use of code mixing between Thai and English language in social media (Facebook) by Thai users. Code mixing is mixing two or more language and only the changing some of elements such as word and phrase in a sentence and usually happens in informal situation and mixing two language or more languages in one situation. The researcher wants to analyze the use of code mixing by Thai users on Facebook because the researcher wants to know the forms and function of using code mixing by Thai users. The techniques of collecting the data used in this research are observation and documentation. The researcher used qualitative observation because the researcher needs to observe the behaviors of using language especially in the use code mixing on Facebook. The documentation is saving and documenting the data which are taken from the observation. The objects of this study are Thai users’ account. The result of this study shows 1) the forms of code mixing 2) the function of code mixing used on Facebook by Thai users. The conclusions of this study are the researcher found six forms of code mixing used by Thai users on Facebook. There are words insertion, phrase insertion, hybrid, repetition, idiom and clause. The researcher found seven function of using code mixing.  That is,  a) to make the caption or status cool or intellect looking, b) to update new English vocabularies to their friends, c) to make the discussion or chatting interesting d) to get a good relation, e) to share information, f) to promote a product to customer, g) to give a proud feeling. Finally, the researcher hopes that this research can be useful to readers and follow up by other researchers because this research is still far from perfect and there are some other aspects that can still be studied in this research. Keywords: : Sociolinguistics, bilingualism, code mixing